(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2021)
Il Fanatismo, La Superstizione and Il Pericolo, poems composed in tercets dating back to 1797, represent the first poetic evidence of Vincenzo Monti’s pro-revolution position. The analysis of the different editions of these textes results in the conclusion that a work of re-writing work has been carried out throughout the entire Jacobean period.